The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/desc.12866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of game‐based and standard executive control training on cognitive and academic abilities in elementary school children

Abstract: Several studies indicate that executive functions (EF), such as working memory (WM), inhibition or flexibility can be improved by training and that these training‐related benefits in WM capacity generalize to reading and mathematical abilities. However, the results of these studies are inconsistent and most of them focused on WM training in children with learning difficulties. Evidence for typically developing children is rare and no study has investigated inhibition training or flexibility training. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 62 publications
6
54
0
6
Order By: Relevance
“…Another disagreement addressed in computer-based training is whether training, including game elements, could enhance the training effects (Doerrenbaecher et al, 2014;Johann and Karbach, 2019). Traditional training refers to training programs using standard cognitive tasks (e.g., Corsi blocktapping task, N-back task) to enhance individuals' cognitive ability (e.g., Espinet et al, 2013;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another disagreement addressed in computer-based training is whether training, including game elements, could enhance the training effects (Doerrenbaecher et al, 2014;Johann and Karbach, 2019). Traditional training refers to training programs using standard cognitive tasks (e.g., Corsi blocktapping task, N-back task) to enhance individuals' cognitive ability (e.g., Espinet et al, 2013;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Baseline cognitive performance was the only factor that predicted cognitive training gains. Some studies with children in middle childhood showed the same association [41,[46][47][48]. In both cases, children with lower baseline cognitive performance were those who benefited the most from the interventions.…”
Section: Individual Differences In the Impact Of Cognitive Interventionsmentioning
confidence: 81%
“…To our knowledge, no other previous study generated different performance profiles from a sample of children and implemented an adapted and adaptive cognitive training intervention for each group. Previous literature focused mostly on the association between individual differences in baseline cognitive measures and training impact, with some studies with children showing how baseline cognitive performance predicted training gains [32,41,46,47]. Nonetheless, in those studies, the same intervention was administered to children without taking these differences into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulating literature suggests lab-based executive function training may not be effective, at least not at obtaining "far transfer" -improvement in related but different domains (Kassai, Futo, Demetrovics, & Takacs, 2019), which is the holy grail of cognitive training. Such training typically involves multiple sessions in which a child completes executive function tasks that ostensibly engage and exercise one or more executive function components (e.g, Johann & Karbach, 2019;Pozuelos, Combita, Abundis, Paz-Alonso, Conejero, et al, 2019). Well-powered training studies with adults often show no evidence of transfer and even sometimes show positive evidence of a lack of transfer (e.g., de Simoni & von Bastian, 2018).…”
Section: Problems With This View Of Executive Function Developmentmentioning
confidence: 99%